2016
DOI: 10.1080/2162402x.2016.1252013
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive CD14+HLA-DRlo/negmonocytes are elevated in pancreatic cancer and “primed” by tumor-derived exosomes

Abstract: Immunological strategies to treat pancreatic cancer offer new therapeutic approaches to improve patient outcomes. Understanding alterations in the immune systems of pancreatic cancer patients will likely lead to advances in immunotherapy for the disease. We profiled peripheral blood leukocytes from pancreatic cancer patients (n D 22) and age-matched controls (n D 20) using flow cytometry. Immune profiling of pancreatic cancer patients identified phenotypic changes in various immune cell populations, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 33 publications
0
51
0
Order By: Relevance
“…Although a recent report demonstrated that PGE 2 -enhanced the expression of PD-L1 on murine F4/80 + macrophages and Ly-6C + myeloid-derived suppressor cells [ 55 ], we did not observe a change in PD-L1 expression on THP-1 macrophages treated with PDAC exosomes. However, others have recently reported that PANC-1 exosomes can reprogram murine J771.A1 macrophages or human monocytes to an M2-like (CD14 + HLA-DR lo , increased Arg1) phenotype [ 56 , 57 ]. Thus, the bioactive lipids from tumor cell exosomes could trigger pro-inflammatory pathways in several TME cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent report demonstrated that PGE 2 -enhanced the expression of PD-L1 on murine F4/80 + macrophages and Ly-6C + myeloid-derived suppressor cells [ 55 ], we did not observe a change in PD-L1 expression on THP-1 macrophages treated with PDAC exosomes. However, others have recently reported that PANC-1 exosomes can reprogram murine J771.A1 macrophages or human monocytes to an M2-like (CD14 + HLA-DR lo , increased Arg1) phenotype [ 56 , 57 ]. Thus, the bioactive lipids from tumor cell exosomes could trigger pro-inflammatory pathways in several TME cell types.…”
Section: Discussionmentioning
confidence: 99%
“…More recent reports also point to this phenomenon, where monocytes stimulated with cancer cell-derived EV become alternatively-activated/M2-type macrophages, expressing elevated levels of VEGF, IL6, Cox2, and arginase-1 amongst many other tumor-supportive factors [92,93] . Similar modulation of myeloid cells are seen using pancreatic cancer exosomes, giving a suppressive CD14 + HLA-DR low/neg phenotype akin to those elevated within the circulation of patients [94] . Similarly, myeloma-derived EV present within the bone marrow microenvironment can activate myeloid-derived suppressor cells (MDSC) and promote progression [95] .…”
Section: Exosome-mediated Antigen Presentationmentioning
confidence: 65%
“…We previously used this systems-based approach to understand the interplay of tumor and immune system interactions. 14 , 15 Additionally, immune biomarkers have been identified in patients with non-small cell lung cancer that predict both survival and treatment-related toxicity after SBRT treatment. 16 In this study, high pretreatment neutrophil-to-lymphocyte ratios and lymphocytopenia were associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 99%